Solving cubic and quartic equations by means of Vieta's formulas - Čojanović, Miloš (JOURNAL OF ADVANCES IN MATHEMATICS, 2025)
In this paper, we will prove that with the use of Vieta's formulas, it is possible to apply a unified method in solving equations of the third and fourth degree.